Short Term Load Forecasting Menggunakan Metode Koefisien - Yosefin Yosefin (Sekolah Tinggi Teknik - PLN, 2020)
Electrical energy has a very important role in national economic growth. With the electrical energy requirements, it is necessary to operate an economical, reliable and quality system. The creation of a template for operating load forecasting for the Java-Bali system uses a coefficient method to calculate weekly loads, daily loads, and loads per ½ hour which is more user friendly. After this Load Forecasting template is applied, the result is a more efficient load deepening in terms of file size and time, and is more effective with the results of the calculation of electric energy (1.71%), electricity load (0.85%), and load factor 79% from planning data and manual realization.